Symmetric full cells assembled by using self-supporting Na3V2(PO4)3 bipolar electrodes for superior sodium energy storage. Issue 19 (20th April 2016) - Zhang, Yi; Zhao, Hongyang; Du, Yaping
Abstract : Self-supporting NVP/ECF electrodes are employed as bipolar materials for the fabrication of symmetric full cells. Abstract : Self-supporting NVP/ECF electrodes are employed as bipolar materials for the fabrication of symmetric full cells. With an output voltage plateau of 1.8 V, these cells give a capacity of 90.2 mA h g −1 at 0.25C with a high energy density of 162 W h kg −1 based on the total mass of the cathode, and retain 81% of the capacity after 280 cycles at 2C.